954 FRAILTY PREVALENCE, TRAJECTORIES AND CLINICAL IMPLICATIONS IN PEOPLE WITH COPD: A SYSTEMATIC REVIEW. (14th June 2022) - Hanlon, P; Guo, X; McGhee, E; Lewsey, J; McAllister, D; Mair, F
Abstract: Background: Frailty is common in people with COPD. This systematic review assesses prevalence and trajectory of frailty and associations with adverse health outcomes in people with COPD. Method: Three databases searched (Medline, Embase and Web of Science) from 2001 to September 2021, supplemented by forward citation searching and hand-searching reference lists. Eligibility criteria were observational studies of frailty (using any measure) in adults (>18 years) with COPD, any setting (community, outpatient, inpatient, rehabilitation, residential care) assessing frailty prevalence, trajectories, or association with health-related outcomes. Study quality was assessed using Newcastle-Ottawa scale. Screening, quality assessment and data extraction performed independently by two reviewers. We synthesized results using narrative synthesis and, where heterogeneity allowed, random-effects meta-analyses. Results: We identified 53 eligible studies using 11 frailty measures. Most common were frailty phenotype (32/53), frailty index (5/53) and Kihon checklist (4/53). Prevalence varied between frailty definitions, setting, and age of study population. Using the frailty phenotype, median prevalence was 12.5% in community studies. Prevalence was higher using other measures, and in inpatients, pulmonary rehabilitation and residential care settings. Frailty in COPD is dynamic, with airflow limitation, dyspnoea, and exacerbation frequency associated with worsening. Improvements in frailty status were observed following pulmonary rehabilitation. Frailty was associated with mortality (5/7 studies), COPD exacerbation (7/11), and hospital admission (3/4). Using frailty phenotype, pooled hazard ratio for mortality was 1.80 (95% CI 1.24–2.63) and pooled incident rate ratios were 1.42 (0.94–2.17) for COPD exacerbation and 1.46 (1.10–1.92) for hospitalization. Frailty was cross-sectionally associated with airflow limitation (11/14), dyspnoea (15/16), COPD severity scores (10/12), poorer QOL (3/4) and disability (1/1). Conclusion: Frailty is a common and dynamic state in COPD, associated with adverse outcomes. However, frailty also appears responsive to intervention. A nuanced understanding of frailty identification, prognosis, and reversibility is required to allow appropriate individualization of COPD care.